Integration of Fiqh al-Lughah and Arabic Semantics in Three Dimensions of Meaning - Martunis; Azhar, Yusron el-Hariq; Ajironi; Hariyadi, Sidiq Tri; Susiawati, Iis (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
The study of meaning in Arabic has developed within two major traditions: fiqh lughah as a classical linguistic heritage and Arabic semantics as a modern linguistic discipline. However, a systematic integration of both traditions into a comprehensive analytical framework encompassing lexical, grammatical, and contextual meanings remains underdeveloped. This article aims to: (1) explain the epistemological relationship between fiqh lughah and Arabic semantics; (2) analyze the three dimensions of meaning in Arabic; and (3) formulate an integrative framework applicable to the interpretation of Arabic texts, particularly religious texts. This study employs a qualitative descriptive approach using library research design, drawing on relevant classical and contemporary sources. The findings reveal that fiqh lughah and Arabic semantics are conceptually interconnected in understanding meaning. Lexical meaning provides the foundational layer through root systems and derivational patterns; grammatical meaning narrows interpretation through i‘rab and syntactic structure; while contextual meaning determines the final interpretation through situational, cultural, and historical analysis. The integration of these three dimensions forms a gradual and circular meaning-construction model that enhances interpretative accuracy in Arabic texts.